Quality consumption of strawberries (Fragaria ananassa) - Carballo, Sergio; Scalone, M.; Borthagary, María (INNOTEC, 2011)
Consumers increasingly require a food product that preserves their nutritional value; retain fresh colour, flavour and texture. Appearance, texture and flavour are attributes identified as to be key to acceptability of fruit and also for consumers in making purchase of fresh produce. The objective of this work was to investigate the consumer's preference of sensory quality and the commercial aspects of fresh strawberries, harvested in spring time from the south of our country, Uruguay- South America. In this study, seven different strawberries varieties (INIA-Arazá, INIA- Ivapitá, Ventana, Seascape, Camarosa, INIA- Ivahé, Aromas) were sensory and physicochemical evaluated. The results obtained showed a high correlation between total soluble solids and sensory attributes (colour, texture, and flavour). Camarosa and Ivahé varieties were prefered for the external and internal aspects of the fruit. Future work should investigate other producer areas of the country and other harvesting time.